2022
DOI: 10.1152/japplphysiol.00660.2021
|View full text |Cite
|
Sign up to set email alerts
|

Development of metabolic and contractile alterations in development of cancer cachexia in female tumor-bearing mice

Abstract: Cancer cachexia (CC) results in impaired muscle function and quality of life and is the primary cause of death for ~20-30% of cancer patients. We demonstrated mitochondrial degeneration as a precursor to CC in male mice, however, if such alterations occur in females is currently unknown. The purpose of this study was to elucidate muscle alterations in CC development in female tumor-bearing mice. 60 female C57BL/6J mice were injected with PBS or Lewis Lung Carcinoma at 8-week age, and tumors developed for 1, 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(61 citation statements)
references
References 48 publications
9
52
0
Order By: Relevance
“…Male mice seem to display more prominent changes in reduction of mitophagy markers, and this could be the result of lesser mitochondrial efficiency or "basal protection" of mitochondria in males compared with females. Recent studies from our group and others support this hypothesis, whereby female mice seem to display blunted oxidative stress through induction of autophagy and mitophagy compared with male mice submitted to hindlimb unloading (Brown et al 2017b;Rosa-Caldwell et al 2020Lim et al 2022). We hypothesize that although mitochondrial biogenesis is elevated, it is not sufficient to improve mitochondrial quality and prevent muscle loss induced by cancer, thus, does not protect from muscle wasting and reduce mRNA content of important mitophagy promoters such as Bnip3 and Beclin possibly reducing clearance of damaged mitochondria noted by increased red puncta.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Male mice seem to display more prominent changes in reduction of mitophagy markers, and this could be the result of lesser mitochondrial efficiency or "basal protection" of mitochondria in males compared with females. Recent studies from our group and others support this hypothesis, whereby female mice seem to display blunted oxidative stress through induction of autophagy and mitophagy compared with male mice submitted to hindlimb unloading (Brown et al 2017b;Rosa-Caldwell et al 2020Lim et al 2022). We hypothesize that although mitochondrial biogenesis is elevated, it is not sufficient to improve mitochondrial quality and prevent muscle loss induced by cancer, thus, does not protect from muscle wasting and reduce mRNA content of important mitophagy promoters such as Bnip3 and Beclin possibly reducing clearance of damaged mitochondria noted by increased red puncta.…”
Section: Discussionmentioning
confidence: 71%
“…Impaired energy metabolism in response to tumor-derived factors and an associated inflammatory response seems to largely influence muscle wasting in CC (Ballarò et al 2021). Studies from our laboratory and others (Asp et al 2010;Brown et al 2017b;Ballarò et al 2021;Lim et al 2022) associate metabolic crisis due to mitochondrial impairments prior to the onset of CC and suggest a connection between mitochondrial aberrations and muscle atrophy preceding CC development. Therefore, promoting mitochondrial health and dynamics represents an interesting target for the development of therapies to prevent or mitigate CC outcomes.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The use of experimental animals followed the 3 R (reduction, replacement, refinement) principles. Because previous studies reported that female animals exhibit estrogen-driven protective responses to the metabolic perturbations and CAC development [ 27 , 28 ], we only used male C57BL/6J mice in this preliminary study to exclude this potential interfering factor. Animals were housed at a room temperature of 22 ± 0.5 °C on a 12 h light and 12 h dark cycle with pair-feeding and free access to water.…”
Section: Methodsmentioning
confidence: 99%